THE EFFECTIVENESS OF REBORES AN PUNISHMENT IN PROMOTING DISCIPLINE AMONG SECONDARY SCHOOL STUDENT - HEMANT KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
It is significant that in recent years, certain responsibilities have been delegated to parties other than the parents. This transfer in authority has taken place. The pressures and adjustments that take place in the child's society have an influence on the child's ability to retain their individuality. In addition, the kid's environment, which includes his parents and other adults, his friends, and his siblings, all have an influence on the child's growth and development. This influence is compounded by the fact that the child is the product of his environment. The numerous pressures of the society in which the youngster lives are mirrored onto him as well since they have an influence on the behaviours of those who are responsible for the kid's upbringing and education. Working together is essential to the success of coaxing a child's development in the right direction. In order to provide the child with an all-encompassing educational experience, both the parent and the teacher need to have a holistic understanding of the child and how he behaves in his everyday life, both at school and at home. This understanding is necessary in order to provide the child with an all-encompassing educational experience.